Low electric current in a bioelectrochemical system facilitates ethanol production from CO using CO-enriched mixed culture - Im, Chaeho; Kim, Minsoo; Kim, Jung Rae; Valgepea, Kaspar; Modin, Oskar; Nygård, Yvonne; Franzén, Carl Johan (Frontiers in Microbiology, 2024)
Fossil resources must be replaced by renewable resources in production systems to mitigate greenhouse gas emissions and combat climate change. Electro-fermentation utilizes a bioelectrochemical system (BES) to valorize industrial and municipal waste. Current electro-fermentation research is mainly focused on microbial electrosynthesis using CO2 for producing commodity chemicals and replacing petroleum-based infrastructures. However, slow production rates and low titers of metabolites during CO2-based microbial electrosynthesis impede its implementation to the real application in the near future. On the other hand, CO is a highly reactive gas and an abundant feedstock discharged from fossil fuel-based industry. Here, we investigated CO and CO2 electrofermentation, using a CO-enriched culture. Fresh cow fecal waste was enriched under an atmosphere of 50% CO and 20% CO2 in N2 using serial cultivation. The CO-enriched culture was dominated by Clostridium autoethanogenum ( 89%) and showed electro-activity in a BES reactor with CO2 sparging. When 50% CO was included in the 20% CO2 gas with 10 mA applied current, acetate and ethanol were produced up to 12.9  2.7 mM and 2.7  1.1 mM, respectively. The coulombic efficiency was estimated to 148% ± 8% without an electron mediator. At 25 mA, the culture showed faster initial growth and acetate production but no ethanol production, and only at 86% ± 4% coulombic efficiency. The maximum optical density (OD) of 10 mA and 25 mA reactors were 0.29 ± 0.07 and 0.41 ± 0.03, respectively, whereas it was 0.77 ± 0.19 without electric current. These results show that CO electro-fermentation at low current can be an alternative way of valorizing industrial waste gas using a bioelectrochemical system.